Civic participation in the legal development of public policies; a propos of the Congress debate on decriminalization of rape-related abortion - Chávez Alvarado, Susana (2015)
In recent years, citizen participation has gradually obtained more importance in the development and application of public policies, expressed in various instruments created. Nevertheless those mechanisms are still incipient, formal and even discursive; many gaps hamper the exercise of citizen opinion, as well as limited use of evidence from academic and technical spaces is achieved. The parliament debate on Let Her Decide Citizen Initiative (citizen proposal to decriminalize rape-related abortion) is a good example to identify the kind of contributions obtained and their potential to generate favorable or unfavorable positions. This analysis pretends to show such positions, acknowledging the road that lies ahead for sexual and reproductive rights laws, especially those on legal and safe abortion, to have consensual human rights contents.